Elevated Carbon Dioxide and Nitrogen Impact Wheat and Its Aphid Pest - Carreras Navarro, Eva; Lam, Shu Kee; Trębicki, Piotr (Frontiers in Plant Science, 2020)
The rise in atmospheric CO2 generally increases wheat biomass and grain yield but decreases its nutritional value. This in turn can alter the metabolic rates, development and performance of insect pests feeding on the crop. However, it is unclear how elevated CO2 (eCO2) and nitrogen (N) input affect insect pest biology through changes in wheat growth and tissue N content. We investigated the effect of three different N application rates (low, medium and high) and two CO2 levels (ambient and elevated) on wheat growth and quality and the development and performance of the bird cherry-oat aphid, a major cereal pest worldwide, under controlled environmental conditions. We found that eCO2 significantly decreased total aphid fecundity and wheat N content by 22% and 39%, respectively, when compared to ambient CO2 (aCO2). Greater N application significantly increased total aphid fecundity as well as plant N content however, did not offset the effects of eCO2. Our findings provide important information on aphid threats under future CO2 conditions, as the heavy infestation of the bird cherry-oat aphid is detrimental to wheat grain yield and quality.